Excellent dispersion stability and enhanced tribological properties of biocarbon‐based magnesium silicate hydroxide modified with oleylamine. (30th January 2022) - Gao, Rongqin; Chang, Qiuying; Wang, Kai
Abstract: Biocarbon‐based magnesium silicate hydroxide (M@C‐ON) was synthesised by hydrothermal method with synthesised magnesium silicate hydroxide (MSH) as the template, glucose as carbon source and oleylamine (ON) as the modified agent. The outstanding dispersion stability of M@C‐ON as lubricant additives in PAO10 with ON as dispersant was proved by accelerated centrifugation and static sedimentation tests. The tribological properties of M@C‐ON as lubricant additive were tested under different concentrations and working conditions, and it was found that oil samples containing M@C‐ON as additive showed enhanced tribological properties than that containing MSH under 600 N, 600 RPM. At the same time, the anti‐wear performance was thought to be affected by the external energy acted on nano‐additives. When M@C‐ON as additive fully functioned, a continuous carbon layer formed on the contact area and the repairing effect of inner MSH of M@C‐ON were considered as the factors to play an anti‐wear role.